The influence of weather and microclimate on Dalbulus maidis (Homoptera: Cicadellidae) flight activity and the incidence of diseases within maize and bean monocultures and bicultures in tropical America - Castro León, Vilma (1992)
Mixed cropping systems in tropical A merica have been shown to be less prone than monocultures to damage from pathogens carried by insects. This finding formed the basis for a series of experiments conducted in Costa Rica to evalueate the hypothesis that mixed cropping systems create a physical environment that influences vector movement and consequently the spread of leafhopper-borne pathogens. The principle finding of the study is that both the mixture of plants and planting density have little influence on the spread of pathogens by Dalbulus maidis, an oligophagus leafhopper which prefers maize, within maize and bean sngle and mized cropping systems. Leafhopper flight activity proved similar for high and low density monocultures and bicultures. The number of leafhoppers immigrating to and emigrating from field appears dependent on the size of the field, not the density of maize plants. Single and mixed crops with the samen density of maize plants were equally prone to damage by pathogens carried by leafhoppers. The lower percentage infection in high density than in low density maize treatments resulted from fewer vector per plant in the former